Impairments in psychological functioning in refugees and asylum seekers - Baumgartner, Josef S.; Renner, Antonia; Wochele-Thoma, Thomas; Wehle, Peter; Barbui, Corrado; Purgato, Marianna; Tedeschi, Federico; Tarsitani, Lorenzo; Roselli, Valentina; Acartürk, Ceren; Uygun, Ersin; Anttila, Minna; et al. (Frontiers in Psychology, 2024)
Refugees are at increased risk for developing psychological impairments due to stressors in the pre-, peri- and post-migration periods. There is limited knowledge on how everyday functioning is affected by migration experience. In a secondary analysis of a study in a sample of refugees and asylum seekers, it was examined how aspects of psychological functioning were differentially affected. 1,101 eligible refugees and asylum seekers in Europe and Türkiye were included in a cross-sectional analysis. Gender, age, education, number of relatives and children living nearby, as well as indicators for depressive and posttraumatic symptoms, quality of life, psychological well-being and functioning, and lifetime potentially traumatic events were assessed. Correlations and multiple regression models with World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) 12-item version’s total and six subdomains’ scores (‘mobility’, ‘life activities’, ‘cognition’, ‘participation’, ‘self-care’, ‘getting along’) as dependent variables were calculated. Tests for multicollinearity and Bonferroni correction were applied. Participants reported highest levels of impairment in ‘mobility’ and ‘participation’, followed by ‘life activities’ and ‘cognition’. Depression and posttraumatic symptoms were independently associated with overall psychological functioning and all subdomains. History of violence and abuse seemed to predict higher impairment in ‘participation’, while past events of being close to death were associated with fewer issues with ‘self-care’. Impairment in psychological functioning in asylum seekers and refugees was related to current psychological symptoms. Mobility and participation issues may explain difficulties arising after resettlement in integration and exchange with host communities in new contexts.